68Ga-FAPI PET/CT in a Patient With Statin-Induced Rhabdomyolysis. (28th January 2023) - Liu, Ya; Guo, Chunmei; Chen, Liming; Huang, Zhanwen
Abstract: Rhabdomyolysis is a syndrome characterized by muscle necrosis and the release of muscle cell contents into blood circulation. There is ample clinical evidence that it is one of the adverse effects of statins. 68 Ga-FAPI PET/CT was performed on a 78-year-old man with newly diagnosed with mediastinal tumor and statin-induced rhabdomyolysis. 68 Ga-FAPI PET/CT showed symmetrical and diffuse increased FAPI uptake in whole-body muscles. Our case indicated that 68 Ga-FAPI PET/CT might be valuable in the evaluation of patients with rhabdomyolysis.